Effect of monolithic zirconia on the degree of conversion of two resin cements analyzed by FT-IR/ATR spectroscopy. Issue 9 (2nd May 2016) - Palta, Nizamettin; Secilmis, Asli; Yazicioglu, Huseyin
Abstract: Objective: This study aimed to evaluate the degree of conversion (DC) of two different resin cements polymerized under the monolithic zirconia specimens in different thicknesses and colors. Material and methods: Partially stabilized monolithic zirconia blocks (inCoris TZI) were cut into three different thicknesses (0.5, 1.0, and 2.0 mm) and the specimens were divided into four color groups (A1, A2, A3, and A4). The light transmittance of each specimen was measured. Panavia F 2.0 or Variolink N resin cement was applied into teflon mold and irradiated using the light emitting diode curing unit for 20 s under monolithic zirconia specimen ( n = 10). The resin cement specimens were stored at room temperature under dry conditions. The DC of each specimen was measured by Fourier transform infrared-attenuated total reflection (FT-IR/ATR) spectroscopy after the 1st and 10th day. Data were analyzed with two-way analysis of variance (ANOVA), two-way repeated measures ANOVA, three-way repeated measures ANOVA, and the Tukey least significant difference (LSD) tests ( α = 0.05). Results: The light-cure resin cement groups showed higher DC than the dual-cure resin cement groups ( p < 0.05). The DC of both resin cements reduced with an increase in the thickness and darkening of the color of monolithic zirconia specimens. There was a statistically meaningful increase in the 10th-day values for dual-cure resin cement ( p < 0.05), whereas there were no significant differences between the 1st- and 10th-day values for light-cure resin cement ( p > 0.05). Conclusion: The use of light-cure resin cement can be suggested for the luting of monolithic zirconia restorations.